An identification method for frequency dependent material properties of viscoelastic sandwich structures. (18th August 2018) - Ledi, K.S.; Hamdaoui, M.; Robin, G.; Daya, E.M.
Abstract: In this paper, an inverse identification method of the viscoelastic material properties (shear modulus G 0 and loss factor η C ) of a symmetric three layered viscoelastic sandwich beam is proposed. Experimental vibration tests are performed to determine resonant frequencies and loss factors for different bending modes. The inverse approach consists into an iterative procedure that determines the mode shapes given the material parameters and then computes the viscoelastic properties from the modes using a Rayleigh quotient until convergence on the material properties is met. As a result, the frequency dependent viscoelastic material properties of sandwich beams are determined in an automated fashion. The method is successfully compared to the Ross-Kerwin-Ungar formulas and to a standard optimization approach. A fit of the viscoelastic material properties is performed providing analytical expressions for these quantities over a wide range of frequencies.